The complete mitochondrial genome of Daurian redstart Phoenicurus auroreus (Aves: Passeriformes: Muscicapidae) - Du, Chao (Mitochondrial DNA B Resour, 2020)
We sequenced the mitochondrial genome of Daurian redstart Phoenicurus auroreus using the next-generation sequencing. The circular genome is 16,832 bp long, encoding 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and a control region. The lengths of rrnL and rrnS were determined to be 1,597 and 984 bp, respectively. The phylogenetic analysis of 18 mitogenomes of Muscicapidae supports monophylies of all genera, including P. auroreus. The information would be useful for understanding the phylogeny and evolution of Muscicapidae.